2017
DOI: 10.18801/jbar.120117.123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators on growth and flowering of tuberose (Polianthes tuberosa L.) cv. single

Abstract: A field experiment was conducted to study the effect of plant growth regulators on growth and yield of tuberose (Polianthes tuberosa L.). Treatments of the experiment were as control (No plant growth regulators), NAA 100 ppm, NAA 200 ppm, NAA 300 ppm, NAA 400 ppm, GA3 100 ppm, GA3 200 ppm, GA3 300 ppm, GA3 400 ppm, 4-CPA 100 ppm, 4-CPA 200 ppm, 4-CPA 300 ppm and 4-CPA 400 ppm. Different concentration of growth regulators showed significant variation on most of the parameters. Tallest tuberose plant (68.9 cm), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
5
8
0
Order By: Relevance
“…Foliar spray with GA 3 200 ppm recorded significantly longest rachis length (39.95 cm) followed by GA 3 100 ppm (39.25 cm) (Table 3). The results are in close conformity with the findings of Rani and Singh (2013), Amin et al, (2017) in tuberose.…”
Section: Length Of Rachis (Cm)supporting
confidence: 93%
See 2 more Smart Citations
“…Foliar spray with GA 3 200 ppm recorded significantly longest rachis length (39.95 cm) followed by GA 3 100 ppm (39.25 cm) (Table 3). The results are in close conformity with the findings of Rani and Singh (2013), Amin et al, (2017) in tuberose.…”
Section: Length Of Rachis (Cm)supporting
confidence: 93%
“…Significantly the longest spike length was noticed at both the concentrations of GA 3 . The results are in line with the findings of Rani and Singh (2013), Sultana et al, (2016), Amin et al, (2017) in tuberose.…”
Section: Length Of Spike (Cm)supporting
confidence: 92%
See 1 more Smart Citation
“…GA 3 has the capability of modifying the growth pattern of treated plants by affecting the DNA and RNA levels, cell division and expansion, biosynthesis of enzymes, protein, carbohydrates and photosynthetic pigments (Ibrahim et al, 2010). Sajid et al, (2016) indicated that vegetative growth and flowering attributes were significantly affected by GA 3 treatments on Chrysanthemum morifolium (Amin et al, 2017). They reported that a rise in vegetative growth and flowering parameters of tuberose were linearly correlated with the increase of concentration of gibberellic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing adaptation of flowers by the farmers has led to the costs and returns from flower cultivation to facilitate the growth of flower cultivation. Amin et al (2017) said it has a great economic potential for cut flower trade and essential oil industry. Tuberose (Polianthes tuberosa L.) is one of the most important tropical ornamental bulbous flowering plants with long lasting flower spikes cultivated for production.…”
Section: Introductionmentioning
confidence: 99%